Research on Organic Nanopore Adsorption Mechanism and Influencing Factors of Shale Oil Reservoirs - Yanfeng He; Guodong Qi; Xiangji Dou; Run Duan; Nan Pan; Luyao Guo; Zhengwu Tao (Geofluids)
The adsorption properties of shale oil are of great significance to the development of shale oil resources. This study is aimed at understanding the microscopic adsorption mechanism of shale oil in organic nanopores. Thus, a molecular model of organic micropore walls and multicomponent fluids of CO2, C4H10, C8H18, and C12H26 is constructed to investigate the adsorption pattern of multicomponent fluids in organic nanopores under different temperature and pore size conditions. The quantity and heat of adsorption are simulated with the Monte Carlo method, which has been used in previous studies for single-or two-component fluids. The results demonstrate that the ability of CO2 to displace various alkanes is different. Specifically, medium-chain n-alkanes are slightly weaker than light alkanes in competitive sorption, and long-chain n-alkanes are less conducive to competitive sorption. The higher the CO2 sorption ratio, the more the sorption sites occupied by CO2. Thus, it is the best replacement for shale oil. The adsorption quantity of carbon dioxide, n-butane, and n-octane in organic nanopores first increases and then decreases as temperature rises. Meanwhile, the adsorption quantity of n-dodecane decreases firstly and then increases. With the increase in the pore size, the adsorption quantity of carbon dioxide, n-butane, and n-octane in organic nanopores increases while the adsorption quantity of n-dodecane first increases and then decreases. Besides, the model with larger pore sizes is more sensitive to pressure changes in the adsorption of carbon dioxide and n-butane than the model with smaller pore sizes. The heat of adsorption is CO2, C12H26, C8H18, and C4H10 in descending order. All are physical adsorption. Moreover, the adsorption quantity of all four components mixed fluid in the organic matter nanopores is positively correlated with the heat of adsorption.